DEVELOPMENT OF DIGITAL COMICS MEDIA BASED ON PROBLEM BASED LEARNING TO INTERNALIZE SOLIDARITY VALUES IN GRADE V STUDENTS AT SD IT AL-MINAH - Ulina Rahmayani; Yakobus Ndona; Zuraida Lubis; Daulat Saragi; Samsidar Tanjung; Winara (SOSIOEDUKASI, 2026)
The phenomenon of character crisis in the form of bullying at the elementary school level reflects a decline in moral values ​​and a dulling of empathy and solidarity among students. This study aims to develop, test the feasibility, practicality, and effectiveness of digital comic media based on Problem-Based Learning (PBL) assisted by Canva to internalize the value of solidarity in fifth-grade students of SD IT Al-Minah. This type of research is research and development (Research and Development) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects involved 21 fifth-grade students. Data were collected through observation, interviews, expert validation questionnaires, education practitioners, student responses, and test instruments (pre-test and post-test). Data analysis techniques were carried out qualitatively and quantitatively. The results of the study show that PBL-based digital comic media meets the following criteria: (1) Very Feasible based on the validation test of material experts by 92% (Very Valid), media experts by 93% (Very Valid), and language experts by 96% (Very Valid); (2) Very Practical based on 93% of teacher responses, 82% of individual student responses (Very Practical), and 87% of large group trials (Very Practical); and (3) Effective based on significant improvements in cognitive and affective learning outcomes. The success of internalizing the value of solidarity was analyzed using Max Scheler's hierarchy of values, which showed a shift in students' behavioral motives from mere sensory pleasure to ethical-spiritual awareness, reflected through indicators of inclusive collaboration, active concern, and sharing. The developed PBL-based digital comic media proved valid, practical, and effective as an innovative instrument to suppress bullying behavior and internalize the value of solidarity at the elementary education level